Training to prevent healthcare associated infections - Dikici, Nebahat; Ural, Onur; Ertap, Fadime; Sumer, Sua; Kara, Fatih (The European Research Journal, 2015)
Objectives. Aim of this study was to investigate pre-education information level, efficiency of training, persistence of acquired information, and factors affecting information level of recently employed nurses about healthcare associated infections.Methods. One hundred and thirty-two nurses who have just started work were trained about “healthcare associated infections and infection control measures”. Tests were performed pre, post training and one year after training. Factors affecting test success were investigated.Results. Nurses who continued education after high school were more successful (p=0.002). Duration of work-hours, unit where they work and presence of previous training didn't affect test success (p=0.705, p=0.040, p=0.105; respectively). Test results were assessed over 100 points. Mean score before the training was 67.95±10.5 and it increased to 85.06±7.6 after the training (p=0.000). Mean test score at test repeated one year later was 80.04±8.77. Unit where they have worked during previous year, application of isolation in their unit and presence of training didn't affect general success in the test (p=0.344, p=0.316, p=0.259; respectively).Conclusions. Training programs using individualized, regularly repeated and approved training methods should be conducted in accordance with needs determined by these studies. Next target after knowledge increase will be reflection of this increase to daily practice and behaviour change.